2023
DOI: 10.1002/adsc.202201285
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal‐Catalyzed Dearomative Vinylation of Electron Rich Benzenes, Naphthalenes and Indoles with Alkynes

Abstract: Dearomatization reactions are among the most efficient chemical processes, combining atom economy, stereospecificity and the ability to generate molecular complexity in a single step. Dearomative vinylation reactions provide a synthetic connection between readily available, simple aromatic starting materials and more unsaturated alkynes. The last decade has witnessed a steady increase in the development of transition metal-catalyzed dearomative vinylation methods of electron rich aromatic compounds with alkyne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…[ 1 , 2 , 3 , 4 , 5 , 6 ] After receiving considerable attention in the synthetic community, Pd(0) and π‐allyl Pd(II) have clearly defined mechanisms. [ 7 , 8 , 9 , 10 , 11 ] The current pathways for Pd‐catalyzed dearomatization of (hetero)arenes are mostly two‐electron processes, requiring harsh reaction conditions, such as high temperature, to overcome the energy barrier of the dearomative insertion step. The preference for more active (hetero)arenes and fused aromatic rings, [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] instead of nonactivated phenyl rings, represents the present state of Pd‐catalyzed dearomatizations ( Scheme 1 a ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 , 2 , 3 , 4 , 5 , 6 ] After receiving considerable attention in the synthetic community, Pd(0) and π‐allyl Pd(II) have clearly defined mechanisms. [ 7 , 8 , 9 , 10 , 11 ] The current pathways for Pd‐catalyzed dearomatization of (hetero)arenes are mostly two‐electron processes, requiring harsh reaction conditions, such as high temperature, to overcome the energy barrier of the dearomative insertion step. The preference for more active (hetero)arenes and fused aromatic rings, [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] instead of nonactivated phenyl rings, represents the present state of Pd‐catalyzed dearomatizations ( Scheme 1 a ).…”
Section: Introductionmentioning
confidence: 99%
“…And many elegant building blocks have been devised to achieve this goal, including 1-indanone and its derivatives, [6][7][8] 1,3-indanedione and its derivatives, 9,10 and others. [11][12][13][14][15][16][17][18][19] As sterling building blocks for the construction of polycyclic indene frameworks, indenedienes have aroused great interest of synthetic chemists due to their unique structural features in the synthesis of polycyclic indene scaffolds, 20 and they could serve not only as four-atom reaction partners in (4 + n) annulation for constructing indene-fused cyclic scaffolds, but also as two-atom reaction partners in (2 + n) annulation for constructing spiroindene scaffolds (Scheme 1b). Recently, our group has been interested in exploiting the reactivities of indene-dienes.…”
mentioning
confidence: 99%
“…With the amount ratio of 1 : 2, a 79% isolated yield of 3a could be obtained (entry 8). Afterward, several representative solvents were evaluated (entries [9][10][11][12][13][14][15][16][17]. The results demonstrated that the solvents had an apparent influence on the yields and 1,2dichloroethane was the best choice for this (4 + 2) cyclization (entry 13).…”
mentioning
confidence: 99%
“…Notably, the unavoidable transformation to stable [4+2] cycloadducts has been inhibited, producing thermodynamically unfavorable [2+2] cycloadducts with outstanding regio-, diastereo-, and enantioselectivities.Aromatic compounds are widely used as important feedstocks in fine and medicinal chemistry research, and many synthetic methodologies for their transformation and functionalization have been developed to convert stable arenes into value-added chemicals. [1][2][3][4][5] Especially, the catalytic asymmetric dearomatization (CADA) has been proven a useful synthetic process enabling conversion of electron polarized aromatic units into enantioenriched motifs. [6][7][8][9] However, the inert aromaticity nature often restricts dearomatizative cycloaddition transformations which otherwise potentially provide one-step access to polycyclic architectures with multiple stereocenters.…”
mentioning
confidence: 99%